CO2 Emission Intensity and Exporting: Evidence from German Firm-Level Data - Philipp Richter; Alexander Schiersch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This study analyses whether exporting firms produce less CO2 emission-intensively than non-exporting competitors. It exploits a novel and unique dataset for Germany, a major exporting country. We make use of the particularity that CO2 emissions are directly linked to the type of fuel consumed. This allows us to directly estimate CO2 emission intensity within a production function framework. We show that such an integrated approach solves the issue of omitted variable bias that standard regressions approaches on CO2 emission intensity of firms are exposed to. It furthermore enables us to apply latest econometric techniques from the productivity literature that solve the problem of endogeneity. Our findings suggest a positive relation between export intensity and CO2 productivity—the inverse of emission intensity. This exporter's environmental premium holds for most of the German manufacturing industries at the two-digit level.
Keywords: F18; D22; L60; 330